Sodobno očetovstvo med plačanim delom in skrbjo za otroke - Humer, Živa (Časopis za kritiko znanosti, 2017)
The article tackles contemporary fatherhood in the context of changing masculinities and the relation between care work and paid work. The main thesis is that the labour market and the position of the individual within it influence the care work of fathers in their private lives. Using the qualitative research of the project "Fathers and employers in action", we show the influence of paid work on two groups of fathers; those in precarious forms of employment and those in leading and managerial positions. In the group of fathers that are in precarious forms of employment, changes in caring fatherhood and variations in the relation between paid work and parenting practices can be observed. Fathers in precarious forms of employment also face the lack of social and workers' rights and are thus in disadvantaged positions when attempting to establish a balance between their work and their personal life. The group of fathers in leading and managerial positions exhibits the prevailing hegemonic masculinity and the breadwinner model with limited participation in the care for children, which can be described as "weekend fatherhood".
Keywords: changes; fatherhood; fathering; labour market; moškost; očetje; očetovanje; očetovstvo; plačano delo; prekarni delavci; prekarno delo; skrbstveno delo; Slovenia; Slovenija; spremembe; starševstvo; trg dela; vodstveni delavci; zaposlitev